PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP HASIL BELAJAR PADA MATERI MENGANALISIS BEARING - Mardani; Debora; Wiyogo (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2019)
Course review horay is one type of cooperative learning. This learning is a test of the understanding of students who use boxes that meet the questions and are numbered to answer them. Students who get the right sign at the earliest immediately shout horror or other yells. The purpose of this study was to study the effect of the course horay review model on the learning outcomes. This study was a pre-experimental with one group pretest-posttest design. The sample of this study was the students of Motorcycle Business (TBSM) which 28 students. The results of the parametric hypothesis test using the t test two correlated samples obtained the value of t count > t table (4,44 > 2,01). Because t count = 4.44 is greater than t table = 2.06, this means that H0 is rejected and H1 is accepted, which means that it relates to the learning model influencing the course review horay model on student learning outcomes